Sounds from the Other Side Afro-South Asian Collaborations in Black Popular Music - Powell, Elliott H. (University of Minnesota Press, 2020)
A sixty-year history of Afro-South Asian musical collaborations. From Beyoncé's South Asian music-inspired Super Bowl Halftime performance, to jazz artists like John and Alice Coltrane's use of Indian song structures and spirituality in their work, to Jay-Z and Missy Elliott's high-profile collaborations with diasporic South Asian artists such as the Panjabi MC and MIA, African American musicians have frequently engaged South Asian cultural productions in the development of Black music culture. Sounds from the Other Side traces such engagements through an interdisciplinary analysis of the political implications of African American musicians' South Asian influence since the 1960s. Elliott H. Powell asks, what happens when we consider Black musicians' South Asian sonic explorations as distinct from those of their white counterparts? He looks to Black musical genres of jazz, funk, and hip hop and examines the work of Miles Davis, John Coltrane, Rick James, OutKast, Timbaland, Beyoncé, and others, showing how Afro-South Asian music in the United States is a dynamic, complex, and contradictory cultural site where comparative racialization, transformative gender and queer politics, and coalition politics intertwine. Powell situates this cultural history within larger global and domestic sociohistorical junctures that link African American and South Asian diasporic communities in the United States. The long historical arc of Afro-South Asian music in Sounds from the Other Side interprets such music-making activities as highly political endeavors, offering an essential conversation about cross-cultural musical exchanges between racially marginalized musicians.